The legacy of Joan W. Moore - Vigil, James Diego (The Oxford handbook of gangs and society, 2024)
Joan W. Moore was trained and tutored at the University of Chicago in the late 1940s to emphasize one thing: community studies, or people and places. Social science does not make sense if the places where people live and work and the environment in which they struggle is ignored. With the guidance and assistance of members of the Chicano community, she embarked on the greatest work of her career: community studies in which male and female gang members work with her side by side. Several major books and numerous scholarly articles resulted from these efforts. The first, Homeboys (1978), and later, Going Down to the Barrio (1991), triggered a slew of research from younger scholars, resulting in a spate of multifaceted studies. A community focus with a collaborative research strategy helped sharpen the focus on why we have gangs: limited mobility, no jobs, and absent maturation paths for youth..